2011
DOI: 10.1007/s11095-011-0499-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Clinical Evidence of the Influence of Sorafenib Binding to Albumin on Sorafenib Disposition in Adult Cancer Patients

Abstract: These findings highlight the major influence of albuminemia on sorafenib clearance and its disposition in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Few studies evaluated the prognostic value of 18 F-fluorodeoxyglucose-PET (18-FDG-PET) in patients receiving antiangiogenic agents for advanced HCC [157,158] . In a small cohort study, Lee et al [159] found that the degree of FGD uptake correlates with outcome in Korean patients with advanced HCC treated with sorafenib.…”
Section: F-fluorodeoxyglucos-petmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies evaluated the prognostic value of 18 F-fluorodeoxyglucose-PET (18-FDG-PET) in patients receiving antiangiogenic agents for advanced HCC [157,158] . In a small cohort study, Lee et al [159] found that the degree of FGD uptake correlates with outcome in Korean patients with advanced HCC treated with sorafenib.…”
Section: F-fluorodeoxyglucos-petmentioning
confidence: 99%
“…Undeniably, such findings should be verified by prospective evaluation in large cohort patients. Finally, no data are/is available regarding the prognostic or predictive value of 18 F-fluorocholine, a PET tracer of lipid metabolism, that is supposed to be more sensitive than 18 F-FDG for HCC detection [158] , in patients receiving antiangiogenic drugs for HCC.…”
Section: F-fluorodeoxyglucos-petmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorafenib is known to bind to albumin resulting in a strong effect on sorafenib clearance in albumine mia and therefore on its disposition in adult cancer patients with advanced solid tumors (17,18). In several pathological states, endogenous ligands may accumulate to relatively high concentrations able to displace drugs highly bound to albumin, resulting in a significant increase in the unbound fraction of drugs (22).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, variations in sorafenib binding may contribute to the variability in sorafenib exposure. A recent study reported the characterization of in vitro sorafenib binding properties to albumin and the effect of albuminemia on sorafenib clearance and its disposition in cancer patients (17). Similar reports have shown that sorafenib is highly protein-bound in human plasma with a higher affinity towards albumin and that limited free drugs may play a role in its borderline clinical activity (18).…”
Section: Introductionmentioning
confidence: 89%